Artemia salina as a new index for assessment of acute cytotoxicity during co-composting of sewage sludge and lignocellulose waste. (April 2016) - El Fels, Loubna; Hafidi, Mohamed; Ouhdouch, Yedir
Highlights: Artemia Salina bioassay as new cytotoxicity index to estimate the toxicity of sludge. Linear correlation between classical parameters with cytotoxicity index during composting. High correlation between phytotoxicity and cytotoxicity during composting. The results encourage the use of Artemia toxicity as new maturity index of compost. Abstract: Considering the necessity to constantly monitor the safety of use of sewage sludge, we have focused on evaluating the toxicity of raw sludge and sludge treated by co-composting with date palm waste using an in vitro assessment of cytotoxicity based on Artemia salina larvae as a simple new sensitive and reliable routine test. The efficiency of co-composting in decreasing sludge toxicity was evaluated in terms of cytotoxicity abatement reaching 100% by the second month of composting for mixture A (1/3 sludge + 2/3 date palm waste) and the third month for mixture B (1/2 sludge + 1/2 date palm waste). Cytotoxicity abatement was confirmed by the increase of germination index, which reached over 100% with positive correlation for lettuce ( R 2  = 0.81 and 0.86) and for turnip ( R 2  = 0.87 and 0.74) for mixtures A and B respectively. A strong correlation between the proposed cytotoxicity test and the evolution of regulatory physical–chemical approaches was found, ( R 2  = 0.88 and 0.89) for NH4 + /NO3 − and ( R 2  = 0.80 and 0.88) for C/N respectively for mixture A and B. These findings allow the inexpensive bioassay reported to be used as a highly sensitive test to determine the cytotoxicity and maturity of composts.